Ultrasmall Integrin‐Targeted Silica Nanoparticles Modulate Signaling Events and Cellular Processes in a Concentration‐Dependent Manner. Issue 14 (3rd December 2014) - Benezra, Miriam; Phillips, Evan; Overholtzer, Michael; Zanzonico, Pat B.; Tuominen, Esa; Wiesner, Ulrich; Bradbury, Michelle S.
<x xml:space="preserve">Abstract</x> Cellular and molecular‐level interactions of nanoparticles with biological systems are a rapidly evolving field requiring an improved understanding of endocytic trafficking as the principal driver and regulator of signaling events and cellular responses. An understanding of these processes is vital to nanomedicine applications. Studies investigating the complex interplay of these processes and their relationship to targeted nanoparticles exploiting endocytic pathways are notably lacking. It is known that integrins traffic through the endosomal pathway and participate in diverse roles controlling signal transduction, cell migration, and proliferation. Here, it is shown that ultrasmall, nontoxic, core–shell silica nanoparticles (C‐dots), surface‐functionalized with cRGDY peptides, modestly activate integrin‐signaling pathways, in turn, promoting the enhancement of cellular functions. First, nanomolar concentrations, two orders of magnitude higher than clinical trial doses, internalize within αvβ3 integrin‐expressing melanoma and endothelial cells, predominantly through an integrin receptor‐dependent endocytic route. Second, integrin‐mediated activation of focal adhesion kinase (FAK) and downstream signaling pathways occurs, in turn, upregulating phosphorylated protein expression levels and promoting concentration‐dependent cellular migration and proliferative activity. Inhibiting FAK catalytic activity leads to decreased phosphorylation levels and cellular migration rates. These findings may inform the design of more effectively‐targeted nanomedicines and provide insights into endocytic regulation of signal transduction.